Epidemiological profile and clinical characteristics of ocular and periocular tumors in North and Central India - Chhavi Gupta; Narendra Patidar; Himanshu Gaikwad; Mihir Mishra; Sima Das (Indian Journal of Ophthalmology)
Purpose: To describe the epidemiological profile and clinical characteristics of ocular and periocular tumors in patients presenting to three tertiary care referral centers in North and Central India. Methods: Hospital-based consortium study. Settings and Design: Retrospective, descriptive, observational study. Results: A total of 3184 patients were diagnosed with 3557 ocular and periocular tumors over 11 years from 2010 to 2021. Of these, 2395 (67.33%) were benign, 84 (2.36%) were premalignant, and 1078 (30.30%) were malignant. The most common location was the ocular surface (n = 1294, 37.09%), followed by the eyelid (n = 1185, 33.97%), intraocular (n = 624, 17.88%), and orbit (n = 454, 13.01%). The most common tumors were retinoblastoma (n = 483, 13.57%), ocular surface squamous neoplasia (OSSN) (n = 301, 8.46%), and dermoid cyst (n = 167, 4.69%). In the pediatric age group, retinoblastoma was the most common tumor (n = 483, 13.57%), while in adults, it was OSSN (n = 301, 8.46%). The stage at presentation for malignant tumors was divided into in-situ (57.14%), local spread (8.16%), and metastasis (32.83%). For specific tumor locations, the stages were 78.83%, 17.51%, and 2.18%, respectively, for eyelid tumors; 51.76%, 27.05%, and 17.64%, respectively, for orbital tumors; 88.37%, 5.81%, and 5.19%, respectively for ocular surface tumors; and 35.71%, 14.15%, and 50.28%, respectively, for intraocular tumors. Conclusions: Identifying the epidemiological characteristics of ocular and periocular tumors will aid in early diagnosis and timely intervention. Intraocular tumors showed delayed diagnosis, advanced stages at presentation, and required patients to travel longer distances for treatment, indicating the need for strengthened diagnostic and treatment facilities to improve access to care.